2002
DOI: 10.1046/j.1365-2133.2002.04720.x
|View full text |Cite
|
Sign up to set email alerts
|

Inflammation is associated with progression of actinic keratoses to squamous cell carcinomas in humans

Abstract: These studies have shown that progression from benign to malignant tumours may be associated with an inflammatory response, which appears to drive malignant conversion, but subsides rapidly following this conversion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
79
4
6

Year Published

2003
2003
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(97 citation statements)
references
References 17 publications
6
79
4
6
Order By: Relevance
“…Furthermore, inflammation and chronic wounds are associated with development of human SCC, as in the development of SCC in burn scars, chronic venous stasis ulcers, and discoid lupus erythematosus (28)(29)(30). Progression of actinic keratosis to SCC has recently also been shown to be associated with an inflammatory stage (31).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, inflammation and chronic wounds are associated with development of human SCC, as in the development of SCC in burn scars, chronic venous stasis ulcers, and discoid lupus erythematosus (28)(29)(30). Progression of actinic keratosis to SCC has recently also been shown to be associated with an inflammatory stage (31).…”
Section: Discussionmentioning
confidence: 99%
“…30,31 Besides, it was observed that the presence of inflamed AKs in humans is associated to the progression to invasive diseases in those lesions. 32 COX-2 and prostaglandin E2 are positive regulators of tumor proliferation, mainly through Ras/Raf/MAPK, and Pt13K/Akt. 33 The MAPK pathway, on the other hand, seems to induce COX-2 production generating a positive feedback cycle.…”
Section: Discussionmentioning
confidence: 99%
“…It is also uncertain whether to interpret inflammation of actinic keratosis as a sign of neoplastic progression or regression (22). In any case the severity of the histological grading of the neoplasm is important to consider.…”
Section: Egfr Inhibitors and Inflamed Actinic Keratosis In Perspectivementioning
confidence: 99%
“…Among them, imiquimod and 5-fluorouracil have proven their efficacy (19). Inflammation is typically present during their regression phase (20,21), but also conversely during progression of actinic keratoses to squamous cell carcinomas (22).…”
Section: Actinic Keratoses and Squamous Cell Carcinomasmentioning
confidence: 99%